Food chemistry - Belitz, H. D. (Springer-Verlag, 1999)
Logically organized according to food constituents and commodities, this updated manual seeks to provide students and researchers in food science or agricultural chemistry with a useful textbook. There are tables for easy reference and a comprehensive subject index.